ETHNOMATHEMATICS IN TAJWID SCIENCE: ANALYSIS OF MATHEMATICS CONCEPTS IN QUR'AN READING LAWS - Adela Zakia Talitha Salma; Nurul Arfinanti (Ethnomath Association in cooperation with Universitas Negeri Yogyakarta, 2025)
The study departs from the understanding that mathematics is often seen as a science discipline that separate from daily-life realities; however, in the contexts of Islamic cultures, specifically in the tajwid science, there is strong relation between mathematics and religious practices. The focus of the present study is revealing how numerical approaches and mathematical patterns are used in the instructional processes of the Koran reading, specifically related to the laws of mad reading. The method used i of the qualitative approach with an ethnograhic research model through in-depth interviews with ustadzs and literary reviews classical and contemporary manuscripts related to the tajwid. Findings show that the tajwid science has integrated the mathematical concepts of duration measurement, rhythm patterns, and numerical ratios in its instructional system, indicating that there are ethnomathematics elements in the contexts of the Moslem cultures. This analysis shows that the numerical approach in the tajwid does not only function as an aid tool, but it also reflects the richness of the Moslem cultures and traditions. This study has widened the understanding that mathematics contextually has a role in the religious practices and instructional processes of the tajwid science.